Conservation genomics of a critically endangered brown seaweed. Issue 4 (27th May 2021) - Mamo, Lea T.; Wood, Georgina; Wheeler, David; Kelaher, Brendan P.; Coleman, Melinda A.
Abstract : Seaweeds provide valuable ecosystem services, but many are undergoing global decline due to climate and anthropogenic stressors. The brown macroalga, Nereia lophocladia (hereafter called Nereia ), is among only a handful of seaweeds globally to be listed as critically endangered and is only described from two known locations, but there exists little knowledge about this species. Here, we combine field surveys to verify the distribution of Nereia, with cutting‐edge genomics to determine genetic diversity and population structure, and inform ongoing conservation actions. We expand Nereia 's known distribution from one to seven locations along a 70‐km long coastal stretch in New South Wales but reveal small population sizes at some sites (as few as 8 individuals despite extensive searching). A total of 1, 261 genome‐wide SNPs were retained from 70 individuals after filtering, and 304 outlier loci under putative selection were detected by one of three methods. Populations showed low genetic diversity (mean expected heterozygosity H E  = 0.055 ± 0.014) and high levels of inbreeding within populations (mean F IS  = 0.721 ± 0.085), along with high genetic differentiation among sites (mean F ST  = 0.276), which may increase susceptibility to future environmental change and decrease the species' ability to recover after loss. Given these findings, we recommend the consideration of both in situ and ex situ conservation measures for Nereia, as well as further research into the species' ecology and biology. Nereia remains of conservation concern and its listing as critically endangered is justified until further investigation elucidates the full distribution and adaptive capacity of the species.